2019
DOI: 10.4018/irmj.2019070104
|View full text |Cite
|
Sign up to set email alerts
|

Do Hotel Responses Matter?

Abstract: This article aims to examine how hotel responses to online reviews influence how potential consumers perceived the helpfulness of the online reviews. Response length and voice were employed to measure the hotel's response quality. 637 reviews with responses were used for empirical analysis. The study identified three different types of response voices: disputed voice, professional voice, and empathetic voice. The results show that both response length and response voice have significant effects on the helpfuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Information overload is usually due to conflicts between individuals with limited information processing capabilities. System function overload occurs when the complexity of the use of technical resources exceeds the addition of new functions [8]. A survey of 298 social media users by the University of Salford found that 66% felt anxious after using social media [8].…”
Section: Social Media and Consumer Sentiment Information Overloadmentioning
confidence: 99%
See 3 more Smart Citations
“…Information overload is usually due to conflicts between individuals with limited information processing capabilities. System function overload occurs when the complexity of the use of technical resources exceeds the addition of new functions [8]. A survey of 298 social media users by the University of Salford found that 66% felt anxious after using social media [8].…”
Section: Social Media and Consumer Sentiment Information Overloadmentioning
confidence: 99%
“…System function overload occurs when the complexity of the use of technical resources exceeds the addition of new functions [8]. A survey of 298 social media users by the University of Salford found that 66% felt anxious after using social media [8]. The effects of social media on emotions can be studied medically, psychologically, and sociologically.…”
Section: Social Media and Consumer Sentiment Information Overloadmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, consumers can obtain information about the occurrence of different situations captured in images. Negative reviews are viewed more than positive reviews and are also perceived as more useful [66,67,77]. Thus, for low ratings or negative emotional reviews, responses with sufficient explanations to long reviews, especially those with embedded images, help reviewers and potential consumers understand the services.…”
Section: Hypothesis 2 (H2) Response Voice Has a Relationship With Comentioning
confidence: 99%